Clinical characteristics of oral lichen planus and its causal context with dental restorative materials and oral health-related quality of life - Linda Daume; Constance Kreis; Lauren Bohner; Susanne Jung; Johannes Kleinheinz (BMC, 2021)
Abstract Background The aim of this study was to investigate the influence of clinical characteristics and dental restorative materials on oral health-related quality of life in patients with oral lichen planus. In particular, the influences of amalgam and metals were investigated. Methods A total of 112 patients with clinical and histological features of oral lichen planus from the Department of Cranio-Maxillofacial Surgery at the University Hospital of Münster participated in this prospective study. Clinical parameters of oral lichen planus and the dental restorative materials used were evaluated. Oral health-related quality of life was investigated by using the short form of the German version of the Oral Health Impact Profile (OHIP-14). In addition, physical pain was rated on a visual analogue scale. Results The average OHIP-14 score was 13.54. A high correlation was seen between OHIP and pain. Likewise, higher OHIP-values were seen for male patients, and such as for those patients with non-reticular forms of oral lichen planus (OLP). A local form of OLP is more often seen on female patients, such as with the presence of reticular lichen. In regard to the restorations, the presence of composite restorations is correlated with a local lichen, whereas the presence of gold restorations is often seen with a generalized lichen. Furthermore, the grading of strength of association between mucosal lesion and amalgam/metal was tested. No significant differences revealed the analysis of the relationship between gender, clinical form of OLP, age, and presentation form between the 4 gradings of Thornhill. Conclusions The oral health-related quality of life is significantly limited in patients with oral lichen planus. But these OHIP scores are not influenced by the restorative materials. Here, pain severity is the most important aspect. We found no statistical differences in the clinical parameters between patients with amalgam or metal restoration and patients without these restorations. It is not necessary to replace amalgam fillings that are not in direct contact with mucosal surfaces.